2008
DOI: 10.1111/j.1365-2230.2008.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining for the differentiation of subungual keratoacanthoma from subungual squamous cell carcinoma

Abstract: SUKAs do not express Ki67 strongly whereas some subungual SCCs do. Thus we conclude that immunohistochemistry for p53 and Ki67 may help distinguish between a subungual SCC and a SUKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 9 publications
1
25
0
1
Order By: Relevance
“…In contrast to other types of keratoacanthomas (out of the ungual region), this type of tumor may not show spontaneous regression, sometimes grows progressively, and can clinically mimic a digital squamous cell carcinoma (SCC). On sonography, a well circumscribed solid-cystic mass that shows a mixed echogenicity pattern (anechoic center and hypoechoic rim), with remodeling or erosion of the bony margins, as well as a posterior acoustic enhancement artifact has been described [ 6,[70][71][72] (Fig. 18.39 ).…”
Section: Solid Tumorsmentioning
confidence: 99%
“…In contrast to other types of keratoacanthomas (out of the ungual region), this type of tumor may not show spontaneous regression, sometimes grows progressively, and can clinically mimic a digital squamous cell carcinoma (SCC). On sonography, a well circumscribed solid-cystic mass that shows a mixed echogenicity pattern (anechoic center and hypoechoic rim), with remodeling or erosion of the bony margins, as well as a posterior acoustic enhancement artifact has been described [ 6,[70][71][72] (Fig. 18.39 ).…”
Section: Solid Tumorsmentioning
confidence: 99%
“…Although dyskeratotic cells were present on histology, given the age of our patient and strong p53 staining in the majority of basal cells,1 the favoured diagnosis was a well-differentiated subungual SCC (figure 2). Subsequent skin cancer multidisciplinary team discussion recommended amputation through the interphalangeal joint.…”
Section: Treatmentmentioning
confidence: 84%
“…Multiple studies have identified significant overexpression of Ki-67 in SCC compared with that in KA (6,7,21,23–26). Scola et al (6) suggested that a Ki-67 fraction of <20% may therefore be indicative of KA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multiple immunohistochemical markers have been investigated to overcome this limitation (5). Proliferation marker protein Ki-67 (Ki-67) is a cell cycle-regulating protein frequently studied in squamoproliferative lesions and the most useful marker among immunohistochemical markers (6,7). Cytokeratin (CK) 17 is a basal/myoepithelial cell-associated keratin protein that is expressed in the outer root sheath of wild-type hair follicles (8).…”
Section: Introductionmentioning
confidence: 99%